Women during the English Reformations
IX, 198 p.
Keywords: Catholic or Protestant, recusant or godly rebel, early modern women reinvented their spiritual and gendered spaces during the reformations in religion in England during the sixteenth century and beyond. These essays explore the ways in which some Englishwomen struggled to erase, rewrite, or reimagine their religious and gender identities.